THE IMPLEMENTATION OF ENGLISH CURRICULUM AT SDN JATIMULYA 11 BEKASI - Luluk Setyowati; Deni Nasir Ahmad; Mal Alfahnum (Universitas Indraprasta PGRI, 2023)
The curriculum changes in Indonesia bring another problem for English subject in Elementary school. The subject can not be found in Kurikulum 2013 (K-13), while it was one of subjects stated in previous curriculum known as KTSP. It becomes current issue in education area. Some people agree that English subject should not be included as subject for Elementary School students, because it is more important for the students to learn Bahasa Indonesia as first and national language. In other hand, some people state that it is important because English is international language that should be learnt by everyone in the world. Then, Elementary School is the right level to start introducing English as foreign language because of the students’ golden age. They will get easier to learn this subject in the next school levels. In fact, English as foreign language is very important to be learnt since early age especially for the students in Elementary School. They have to learn English in line with Bahasa Indonesia that being learnt as their first language. Elementary School students as young learners need to get English as one of subject in their school, because they have high interest in learning new things such as English that starting commonly used in daily life. So, it is important to take English as one of subject in Elementary School curriculum with several considerations